Analisis Sumber Dan Penggunaan Modal Koperasi - Indianti, Iie (Universitas Koperasi Indonesia, 2023)
This research was conducted at the Pesantren Darul Fatwa Cooperative. The purpose of this study is to determine the sources and uses of working capital in cooperatives. This study uses a qualitative descriptive approach with cooperative guidance on financial reports during the 2019-2021 research period. Analysis of the data used in this study is the analysis of sources and use of working capital with sequential financial reports. The results show that the annual source of capital increases and every year a lot of working capital is not used or used.